MANFAAT KANDUNGAN INFORMASI AMORTISASI GOODWILL DALAM LAPORAN KEUANGAN - Anindhita, Anggara A.; Martani, Dwi (UI Scholars Hub, 2006)
Indonesian GAAP No.22 Accounting fo r Business Combinations requires that goodwill arises from acquisition should be amortized over its economic life for 5 years, or can be extended fo r maximum 20 years if there is any proper reason. Meanwhile, Statement o f Financial Accounting Standard (SFAS) No. 142 Good will and Other Intangible Assets and International Financial Reporting Standards (IFRS) No. 3 Business Combinations had changed the requirement o f accounting treatment fo r goodwill. They require that goodwill should not be amortized, but is subject to impairment test periodically. The reasons o f this treatment are that the economic life o f goodwill cannot be reliably estimated and its pattern fo r decrease in value changes overtime. This research is intended to examine the implication o f goodwill amortiza tion on investors ’decisions in all industries in general and in manufacturing indus try in particular, in Indonesia. This is achieved by comparing the ability o f earnings after amortization before extraordinary items, earnings before amortization and extraordinary items, and cash flow from operation in explaining market-adjusted return. The result shows that goodwill amortization only contribute minor impact to the market-adjusted return, which agrees the prior researches conclusions.